Removal of dyes by using pumpkin seeds as adsorbent: article - Zuhairi, Ahmad Mujahid Hakimy; Jafri, Hasnora (2019)
Adsorption method was commonly applied in wastewater treatment to remove dyes due to its simplicity of design and ease of operation. However, the cost of conventional adsorbent such as activated carbon is too high and required additives to improve it efficiency. Because of that, many agriculture waste had been studied as potential adsorbent to replace the current conventional adsorbent. Thus the aimed of this research is to prepared eight types of adsorbent from pumpkin seeds, and used it in adsorption process to determine the effectiveness of the adsorbents to remove basic dye methylene blue (MB) and acidic dye methyl orange (MO) from simulated wastewater. The pumpkin seeds were subjected into two type of treatments which are physical and chemical treatments. After the adsorbent preparation was completed, Fourier transform infrared spectroscopy (FTIR) was used to determine the number and positions of the functional groups available on adsorbent surface. In this research, the effect of adsorbent dosage, contact time and initial dyes concentration were studied toward percentage removal of dyes. The results showed that, as the adsorbents dosage, contact time and dyes initial concentration were increased, the percentage removal of dyes also increased. This research can be further used to design adsorption columns for dyes removal